Stereotip Masyarakat Asli Kao Terhadap Pendatang Trans Jawa ( Studi Komunikasi Antar Budaya di Desa Toliwang Kecamatan Kao Barat Kabupaten Halmahera Utara ) - Bahry, Syaiful; Bailussy, Wahyuni; Simabur, Lisda A.; Kahar, Suyatno; Suwarjito, Suwarjito (Jurnal Ilmiah Global Education, 2024)
This research is based on the stereotype of Toliwang people, west Kao district, to the Javanese Immigrants. But lack of information or knowledge, so the word "stereotype" become negative meaning. This study aims at describing how the Kao native people's stereotype against Javanese immigrants in Toliwang, west Kao district. The used method in this study is qualitative descriptive that aims to interpret and solve problems researched, by describing the reserch objects based on the existing evidences. The research result shown that, the Kao people stereotype is emerged caused by some factors, namely: behaviour, miscommunication, and envy. These factors exist caused by the people's daily and friendship from Javanese immigrants against local people. By the obtained data from informan, there are some stereotypes that emerge on the Javanese immigrants as follow: Javanese are dirty, Javanese are invaders, and Javanese are introvert. These stereotypes are shaped cannot be separated from behaviour, background, interaction, and knowledge that owned by the Kao people themselves. These things, then, become a view of informan is same or different. Generally, by all informans have same in the shape of interaction experience with Javanese immigrants, and such the distintion between native people and comer. Based on the research result, it can draw conclusion that: stereotype is not only viewed as finished result, but also but the process of social identity categorization inside of an individual which get involved and considering consepts or themes become reference in shaping stereotype.